Survey of Student Learning Interest PJOK Learning at Junior High School - Rahayu, Windia; Yusfi, Herri; Victorian, Ahmad Richard; Destriani, Destriani; Nanda, Fitri Agung; Azhar, Samsul; García-Jiménez, José Vicente (Jurnal Pendidikan Jasmani Indonesia, 2023)
Education is a process of seeking information that can be obtained by all students in the process of advancing national development. This research uses descriptive research with a quantitative approach, and the method used is a survey with a questionnaire as data collection. The research population was all students, with the sample used being class VII totaling 374 students at SMP Negeri 29 Palembang studying Physical Education, Sports and Health (PJOK) for the 2023/2024 academic year. The results of the research show that students interest in learning at SMP Negeri 29 Palembang towards Physical Education Sports and Health (PJOK) learning carried out at school is in the very high category. Judging from the interest of the students themselves who feel happy when learning takes place, the variety of teachers who are not monotonous when providing learning material and the infrastructure factors that support the continuity of learning process at school.